Long-Term Changes in Mehlich-3-Extractable Sulfur and Magnesium under Intensive Agriculture in Eastern Canada. Issue 20 (13th November 2019) - Nyiraneza, Judith; Thompson, Barry; He, Juanxia; Stiles, Kyra; Geng, Xiaoyuan; Jiang, Yefang; Fillmore, Sherry
ABSTRACT: Leachable nutrients such as sulfur (S) and magnesium (Mg) may become limiting under temperate regions with sandy soils. This long-term georeferenced study assessed changes in Mehlich-3-extractable S and Mg in the province of Prince Edward Island (PEI), Canada. The Island was sampled over 3 years (one cycle, over 500 sampling points) from 1998 to 2015 for a total of six cycles. Regression kriging was used as a method of interpolation. Sulfur in the high category (>25 mg kg −1 ) dominated during the first two cycles (69%–98% of the total area) and then decreased below 1% of the total area during the last two cycles. The area in the low to medium category (7–18.50 mg kg −1 ) represented less than 1% of the total area in the first three cycles and increased to 84% in the last cycle. Magnesium distribution was dominated by soils within the low to medium range (36–116 mg kg −1 ), representing 74% to 97% of the total area from cycle 1 to cycle 6, respectively. Areas within the Mg range of 116 to 196 mg kg −1 changed from 24% of the total area in cycle 1 to 3% of the total area by the end of cycle 6. The S and Mg contents were positively correlated to soil organic carbon and negatively correlated to phosphorus. In a temperate climate and sandy loam soils, S and Mg decline over time under intensive cultivation, and the soil supply alone may not meet the crop S and Mg requirements. Abbreviations : Al: aluminum; C: carbon; CEC: cation-exchange capacity; CV: coefficient of variation; DEM: digital elevation model; Fe: iron; GIS: geographic information system; GPS: Global Positioning System; K: potassium; Mg: magnesium (extracted by Mehlich-3 solution); N: nitrogen; OK: ordinary kriging; P: phosphorus; PEI: Prince Edward Island; RK: regression kriging; RMSE: root mean square error; S: sulfur (extracted by Mehlich-3 solution); SOC: soil organic carbon; SOM: Soil Organic Matter.